Synthesis and Characterization of Ag/PEDOT:PSS Films Used for NH\(_3\) Selective Sensing - Dinh, Nguyen Nang; Long, Lam Minh; Thu, Hoang Thi; Hoa, Huynh tran My; Trung, Tran Quang (Communications in Physics, 2016)
Nano-Ag/PEDOT-PSS films were prepared by spin-coating technique. SEM surface morphology, Raman spectra and gas sensing of methanol, humidity and NH3 were studied. The obtained results showed that the resistance of Ag/PEDOT:PSS sheets exposed to gases related to the generation of electrons from the gases adsorption that eliminated holes as the major carriers in PEDOT:PSS. For NH3 gas the largest change of the resistance of Ag/PEDOT:PSS was observed. The less sensitivity of humidity and ethanol sensing was explained due to less dedoping reaction between H2O and ethanol vapor with Ag/PEDOT:PSS, respectively. This suggests a potential application of the nano-Ag/PEDOT-PSS sensors for  the selective monitoring NH3 gas in environment.